Identifying the Rebound - Evidence from a German Household Panel - Manuel Frondel; Jörg Peters; Colin Vance (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2007)
Using a panel of household travel diary data collected in Germany between 1997 and 2005, this study assesses the effectiveness of fuel efficiency improvements by econometrically estimating the rebound effect, which measures the extent to which higher efficiency causes additional travel.Following a theoretical discussion outlining three alternative definitions of the rebound effect, the econometric analysis generates corresponding estimates using panel methods to control for the effects of unobservables that could otherwise produce spurious results. Our results, which range between 57% and 67%, indicate a rebound that is substantially larger than obtained in other studies, calling into question the efficacy of policies targeted at reducing energy consumption via technological efficiency.
Keywords: D13; Q41; 330; Automobile travel; rebound effect; panel models; Energiesparen; Konsumentenverhalten; Verkehrsökologie; Verkehrsverhalten; Privater Haushalt; Panel; Deutschland